Fast spin-echo MR in the detection of vertebral metastases: comparison of three sequences. - Jones, K M; Schwartz, R B; Mantello, M T; Ahn, S S; Khorasani, R; Mukherji, S; Oshio, K; Mulkern, R V (American Journal of Neuroradiology, 1994)
PURPOSE To examine the relative capabilities for the detection of vertebral metastases of three available fast spin-echo sequences: T1-weighted fast spin-echo, short tau inversion recovery (STIR) fast spin-echo, and T2-weighted fast spin-echo sequences with chemical shift selective saturation pulse fat suppression. METHODS Fourteen patients were evaluated prospectively over a 2-month period with T1-weighted fast spin-echo (four echo train, four acquisitions, 1 min 59 sec-2 min 37 sec). STIR fast spin-echo (16 echo train, four acquisitions, 2 min 30 sec-3 min 19 sec), and T2-weighted fast spin-echo (16 echo train, 4 acquisitions, 2 min 27 sec-3 min 16 sec). For all three pulse sequences, measurements were obtained of the signal intensities of normal marrow, abnormal marrow, fat, and noise posterior to the spine. Contrast-to-noise ratios were calculated for metastases in each case. Lesions were evaluated by three observers and rated for size, location, and conspicuity. RESULTS Signal intensities of fat, normal marrow, and noise were highest for T1-weighted fast spin-echo sequences. STIR fast spin-echo and fat-suppressed T2-weighted fast spin-echo had approximately similar fat-suppression capabilities. Though contrast-to-noise ratios were highest overall for STIR fast spin-echo, the finding was not statistically significant and lesion conspicuity was deemed better with fat-suppressed T2-weighted fast spin-echo and T1-weighted fast spin-echo images. Discrete lesions were well identified on all three pulse sequences. CONCLUSION Fast spin-echo sequences appear promising for the detection of vertebral metastases. Further work should be directed toward comparison with conventional spin-echo to determine whether fast spin-echo may replace conventional spin-echo sequences for evaluation of vertebral metastases.